2014
DOI: 10.1038/nrmicro3289
|View full text |Cite
|
Sign up to set email alerts
|

The elemental composition of virus particles: implications for marine biogeochemical cycles

Abstract: In marine environments, virus-mediated lysis of host cells leads to the release of cellular carbon and nutrients and is hypothesized to be a major driver of carbon recycling on a global scale. However, efforts to characterize the effects of viruses on nutrient cycles have overlooked the geochemical potential of the virus particles themselves, particularly with respect to their phosphorus content. In this Analysis article, we use a biophysical scaling model of intact virus particles that has been validated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
295
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 297 publications
(309 citation statements)
references
References 77 publications
9
295
2
3
Order By: Relevance
“…The C/N ratio of phages (3.00) is predicted to be lower than that of bacteria (4.25) (Vrede et al, 2002;Chan et al, 2012;Jover et al, 2014). Quantitative estimates indicated that phage particles represented a significant portion of redistributed C and N in our experiment, and as a result of phage production these elements were incorporated into biological particles (cells and phages) at greater, but disproportionate, amounts compared with control populations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The C/N ratio of phages (3.00) is predicted to be lower than that of bacteria (4.25) (Vrede et al, 2002;Chan et al, 2012;Jover et al, 2014). Quantitative estimates indicated that phage particles represented a significant portion of redistributed C and N in our experiment, and as a result of phage production these elements were incorporated into biological particles (cells and phages) at greater, but disproportionate, amounts compared with control populations.…”
Section: Discussionmentioning
confidence: 81%
“…The total masses of bacteria (cellular) and phage C and N were calculated using previously reported elemental estimates of 0.2 fg C and 0.076 fg N per phage and 149 fg C and 35 fg N per cell (Heldal et al, 1985;Vrede et al, 2002;Chan et al, 2012;Jover et al, 2014). At the final time point, cells in the control culture contained 76.74 (±10.43) and 18.0 (±2.45) mg l À 1 of C and N, respectively (Figures 1b and c).…”
Section: Stoichiometric Shifts In Carbon and Nitrogen Associated Withmentioning
confidence: 99%
“…Next, it is noteworthy that virus-host interactions unfold in a dynamic landscape of multiple nutrients, both organic and inorganic. A recent study suggested that virus lysis may be limited by phosphorus availability within hosts (Jover et al, 2014). Hence, viral lysis may transform (not just shunt) elements back into the microbial loop (Weitz and Wilhelm, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiol. 12, 519-528 (2014)) 1 , Jover et al highlight the generally overlooked potential biogeochemical importance of the elements that are bound in virus particles. Here, we wish to discuss the fate of marine virioplankton (that is, free virus particles in the water column), which further extends our knowledge of the biogeochemical cycling of the elements that are present in viral particles in the ocean.…”
mentioning
confidence: 99%
“…This rapid turnover rate of marine virioplankton suggests that the chemical elements within these particles also undergo fast and active cycling. Jover et al suggest that these elements, particularly phosphorus, could make a considerable contribution to marine elemental reservoirs 1 . In fact, the direction of flow and biogeochemical cycling of these elements depends on the fate of the virioplankton (FIG.…”
mentioning
confidence: 99%